1971
DOI: 10.4049/jimmunol.107.3.832
|View full text |Cite
|
Sign up to set email alerts
|

Precipitating Antibody to Group a Streptococcal Polysaccharide in Humans

Abstract: A simple method for detecting and quantitating antibodies against streptococal group A carbohydrate (A-CHO) is described. Its limits of sensitivity were determined as 0.84 µg Ab N/ml and 0.6 µg/ml A-CHO antigen (Ag). The precipitating activity was specifically inhibited by N-acetyl-glucosamine and was associated with the serum fraction precipitated by half-saturated ammonium sulfate and by the 7S pool obtained by gel filtration on Sephadex G-200. The method was highly reproducible using blind duplicates on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Earlier mouse immunization studies with protein-conjugated native or synthetic GAC vaccines show clear efficacy against multiple GAS M types 29,30 . Serum anti-GAC antibodies are likewise present in healthy individuals and peak around 17 years of age, strongly correlating with decreased GAS infection risk 31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier mouse immunization studies with protein-conjugated native or synthetic GAC vaccines show clear efficacy against multiple GAS M types 29,30 . Serum anti-GAC antibodies are likewise present in healthy individuals and peak around 17 years of age, strongly correlating with decreased GAS infection risk 31 …”
Section: Introductionmentioning
confidence: 99%
“…29,30 Serum anti-GAC antibodies are likewise present in healthy individuals and peak around 17 years of age, strongly correlating with decreased GAS infection risk. 31 For the above reasons of immunogenicity and conservation, GAC has garnered considerable interest as a universal GAS vaccine antigen. However, this has also elicited concern, since experimental evidence for autoreactivity of antibodies that recognize the native GAC GlcNAc side chain against human tissues has been communicated by different research groups.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by immunising mice with GAC conjugated to tetanus toxoid (TT) or CRM , a mutant version of the diphtheria toxin) carrier proteins, protection was conferred against challenge with live Strep A (Kabanova et al, 2010;Sabharwal et al, 2006). It has been reported that colonization of Strep A in human throats is inversely correlated with the levels of anti-GAC antibodies (Sabharwal et al, 2006) that peak at around age 17 in correspondence to the reduced incidence of Strep A infection (Zimmerman, Auernheimer, & Taranta, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Immunological studies have revealed that GAC is accessible to antibody binding 14 , 31 , 32 , with affinity-purified anti-GAC antibodies showing opsonic properties specifically against M3, M6, M14 and M28 serotypes 32 . Host infection with Strep A induces circulating GAC specific antibodies, which may be slow to generate initially, but are thought to gradually increase with age, peaking in adolescents 33 . Some studies suggest the GlcNAc sidechain portion of the polymer 32 , particularly the branch points within the trisaccharide repeat structure, to be important in recognition and generation of opsonophagocytic IgG antibodies 22 , 32 , 34 .…”
Section: Introductionmentioning
confidence: 99%